Erosion and marginalization in Pahuatlán municipality, Puebla: A binomial of causality? - Rosalía Castelán Vega (Investigaciones Geográficas (Mx), 2011)
An understanding of the interaction between deterioration of the environment and marginalization of communities is essential in order to formulate public policies that will combine social and environmental objectives. The aim of the present study was to explore the relationship between erosion and marginalization in the municipality of Pahuatlán, Puebla, Mexico. The erosion was assessed by the methods developed by FAO and Ruiz et al. Marginalization was determined by the Consejo Nacional de Población (CONAPO) method using Instituto Nacional de Estadística, Geografía e Informática (INEGI) indicators. The relationship was established by a simple correspondence analysis and was confirmed by Pearson's Chi-square test. Erosion could be assigned to one of three grades: moderate, severe and very severe. In the 32 towns that constitute the municipality, marginalization was moderate in 5, severe in 14 and very severe in 13. The correspondence analysis and the Chi-square test showed a causal relationship between erosion and marginalization, although it was not possible to detect with certainty which is the cause and which the effect. However, the results can contribute to the design of sustainable strategies for the municipality.